2,6-Dimethylbenzoquinone as a New Enzymatic Spectrophotometric Indicator for the Assessment of the Organophosphate Impact on Cholinesterase Biomarker of Duck - Chen, Jin; Wang, Yuhui; Cui, Shumin; Miao, Jigen (Asian Journal of Chemistry, 2012)
Changes in biomarkers of a duck serum from stressed environments represent a reliable tool in evaluating toxious effect of cropland biogeocenose. A new and alternative enzymatic spectrophotometric indicator, 2,6-dimethylbenzoquinone (2,6-DMBQ) was explored to assess the organophosphate impact on cholinesterase (ChE) from duck serum. The enzymatic activity could be assessed by measuring the absorbance decrease at 257 nm wavelength and the decrease of enzymatic activity is related with the inhibiton of parathion methyl on cholinesterase.